Bryozoa from deep-sea habitats of the northern Gulf of Cádiz (Northeastern Atlantic) - Ramalho, Laís V.; López-Fé, Carlos M.; Mateo-Ramírez, Angel; Rueda, José Luis (Zootaxa, 2020)
This study examines material collected in the northern part of the Gulf of Cádiz, in the Northeastern Atlantic Ocean, between the Iberian Peninsula and northern Africa, at 300–1200 m depth, within the Site of Community Importance “Volcanes de fango del Golfo de Cádiz” (Mud volcanoes of the Gulf of Cádiz, ESZZ-12002). Several previous studies were carried out in the Iberian Peninsula and Moroccan area (shallow and deep waters), recording ca. 300 bryozoan species from the Gulf of Cádiz. In the present study a total of 40 bryozoan taxa were identified, including two species new to science—Antropora gemarita n. sp. and Microporella funbio n. sp.—and three new records for the area.